Does garlic oil have a role in the tratment of Helicobacter pylori infection - Ahmet AYDIN; Galip ERSÖZ; Oktay TEKEŞİN and Eren AKÇİÇEK and Müge TUNÇYÜREK and Yücel BATUR (Turkish Journal of Gastroenterology, 2019)
-